2016
DOI: 10.1155/2016/5314719
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Choice of Peritoneal Dialysis in Patients with End-Stage Renal Disease

Abstract: Background. The purpose of this study was to analyze the factors associated with receiving peritoneal dialysis (PD) in patients with incident end-stage renal disease (ESRD) in a hospital in Southern Taiwan. Methods. The study included all consecutive patients with incident ESRD who participated in a multidisciplinary predialysis education (MPE) program and started their first dialysis therapy between January 1, 2008, and June 30, 2013, in the study hospital. We provided small group teaching sessions to advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 38 publications
2
17
1
3
Order By: Relevance
“…Many of these patients wish for a more extensive discussion of their dialysis modality choices before dialysis initiation (28,30). Unplanned start on PD is considered a safe and efficient alternative to unplanned HD, even in the elderly (29,(31)(32)(33), and decreases the need for temporary tunneled dialysis catheter for HD, without increasing hospital stays (13,34).…”
Section: Unplanned Dialysismentioning
confidence: 99%
“…Many of these patients wish for a more extensive discussion of their dialysis modality choices before dialysis initiation (28,30). Unplanned start on PD is considered a safe and efficient alternative to unplanned HD, even in the elderly (29,(31)(32)(33), and decreases the need for temporary tunneled dialysis catheter for HD, without increasing hospital stays (13,34).…”
Section: Unplanned Dialysismentioning
confidence: 99%
“…Looking at patient-related characteristics, the international literature shows, that due to only a few absolute contraindications against PD, most ESRD patients are eligible for both modalities [ 10 , 11 ]. Nevertheless, several studies have identified differences in educational level and gender between HD and PD patients [ 5 , 12 15 ], and the majority of prior research indicates PD patients to be younger [ 2 , 3 , 12 17 ]. Other patient-related factors, like personality traits or attitudes, and their role in the context of dialysis modality choice have hardly been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identi ied several factors associated with RRT selection, including the timing of referral, physician bias, predialysis education, resource availability, social and cultural status [4][5][6]. In contrast, a recently published registry study show that patients with early awareness of the method [7] were more likely to select self care dialysis and avoid unnecessary invasive procedures.…”
Section: Introductionmentioning
confidence: 99%